Convergent evolution of sperm gigantism and the developmental origins of sperm size variability in Caenorhabditis nematodes. (1st November 2016) - Vielle, Anne; Callemeyn‐Torre, Nicolas; Gimond, Clotilde; Poullet, Nausicaa; Gray, Jeremy C.; Cutter, Asher D.; Braendle, Christian
Abstract: Sperm cells provide essential, if usually diminutive, ingredients to successful sexual reproduction. Despite this conserved function, sperm competition and coevolution with female traits can drive spectacular morphological change in these cells. Here, we characterize four repeated instances of convergent evolution of sperm gigantism in Caenorhabditis nematodes using phylogenetic comparative methods on 26 species. Species at the extreme end of the 50‐fold range of sperm‐cell volumes across the genus have sperm capable of comprising up to 5% of egg‐cell volume, representing severe attenuation of the magnitude of anisogamy. Furthermore, we uncover significant differences in mean and variance of sperm size among genotypes, between sexes, and within and between individuals of identical genotypes. We demonstrate that the developmental basis of sperm size variation, both within and between species, becomes established during an early stage of sperm development at the formation of primary spermatocytes, while subsequent meiotic divisions contribute little further sperm size variability. These findings provide first insights into the developmental determinants of inter‐ and intraspecific sperm size differences in Caenorhabditis . We hypothesize that life history and ecological differences among species favored the evolution of alternative sperm competition strategies toward either many smaller sperm or fewer larger sperm.